Accounting reform and value relevance of financial reporting from non-financial listed firms on the Vietnam stock market - Huu Anh Nguyen; Thi Tra Giang Dang (Cogent Business & Management, 2023)
The research questions that are solved in this paper are as follows: (1) how the value relevance of accounting information evolved from a developing country perspective and (2) how the accounting reform impacts on value relevance. This study aims to assess the value relevance of accounting information released by non-financial firms listed on the Vietnam stock exchange for the period of 2010-2020. Our paper will contribute more supportive empirical evidence about the usefulness of value relevance research through doing research in Vietnam as a developing country, where experiences switching from a planned economy to an open economy and the regulations change continuously. We provide useful literature overview and important implications for both equity investors and standard setters. Based on usefulness information theory and asymmetric information theory, research hypotheses are designed. The study then uses the Ohlson price model to test these hypotheses. In the model, the explanatory variables, namely, book value per share, earnings per share, and share prices as independent variable, are examined; panel corrected standard error estimator (PCSE) is applied. The findings reveal that both earnings and book value of equity exhibit a positive and significant effect on stock prices. Earnings explain the higher variation in stock market values on the Vietnam Stock Exchange compared to book value of equity. The study, however, finds a decreasing trend in the change of the value relevance over the period 2010-2020 and accounting reforms in 2014 did not improve the value relevance.
Keywords: 650; emerging market; stock price; accounting standard; Price model; value relevance